2018
DOI: 10.1002/chem.201803477
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Synergistic Heterobimetallic (Na–Mg) and Homometallic (Na or Mg) Bases in Metallation Reactions of Dialkylphenylphosphines and Dialkylanilines: Lateral versus Ring Selectivities

Abstract: A series of dialkylphenylphosphines and their analogous aniline substrates have been metallated with the synergistic mixed-metal base [(TMEDA)Na(TMP)(CH SiMe )Mg(TMP)] 1. Different metallation regioselectivities for the substrates were observed, with predominately lateral or meta-magnesiated products isolated from solution. Three novel heterobimetallic complexes [(TMEDA)Na(TMP)(CH PCH Ph)Mg(TMP)] 2, [(TMEDA)Na(TMP)(m-C H PiPr )Mg(TMP)] 3 and [(TMEDA)Na(TMP)(m-C H NEt )Mg(TMP)]  4 and two homometallic complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(146 reference statements)
1
4
0
Order By: Relevance
“…Proton-decoupled 31 P( 1 H) NMR spectra showed resonance between ~−7 ppm and −27 ppm (Supplementary Materials), which was significantly dependent upon the substituents (the more basic the phosphine, the more up-field the signal in the 31 P NMR spectra). In the past, one-or multi-step synthesis of compounds (2) [16,17] (3) [18], (4) [19], (5) [20], (7) [21], (9) [22], (10) [23], and (11) [24] has been reported, including by the Grignard method, with which our results match well. Moreover, in our method, the yields were comparable to the transition-metal-mediated synthesis with equally broad scope.…”
Section: Synthesissupporting
confidence: 84%
“…Proton-decoupled 31 P( 1 H) NMR spectra showed resonance between ~−7 ppm and −27 ppm (Supplementary Materials), which was significantly dependent upon the substituents (the more basic the phosphine, the more up-field the signal in the 31 P NMR spectra). In the past, one-or multi-step synthesis of compounds (2) [16,17] (3) [18], (4) [19], (5) [20], (7) [21], (9) [22], (10) [23], and (11) [24] has been reported, including by the Grignard method, with which our results match well. Moreover, in our method, the yields were comparable to the transition-metal-mediated synthesis with equally broad scope.…”
Section: Synthesissupporting
confidence: 84%
“…Similarly, molecules in 37 106 and 44 113 The molecules in 50, 119 51, 120 52, 121 53, 122 54, 123 55, 124 56 125 and 57 126 each carry two iodide substituents, see Fig. 6 for chemical diagrams.…”
Section: Zero-dimensional Aggregates Sustained By Two C-i•••π(arene) mentioning
confidence: 99%
“…The first category involves crystals 1, 70 4, 73 48, 117 51, 120 105, 169 155, 205 160, 222 164 226 and 181. 238 Of the nine crystals, five have congeners having C-X•••π(arene) interactions and of these, congeners of 4, 73 i.e.…”
Section: Likelihood Of Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this concept, Hagadorn showed that TMP 2 Zn is an excellent base for the α-zincation of various carbonyl compounds and the metalation of pyridine-N-oxide in toluene 34,35 . Similarly, Mulvey and co-workers [36][37][38][39][40][41][42][43] reported several mixed bimetallic amide bases for metalation reactions in non-coordinating hydrocarbon solvents. Herein we report a highly selective and broadly applicable magnesiation of various aryl azoles using the amide base TMPMgBu in a toluene/hexane solvent mixture and subsequent cross-couplings and electrophilic quench reactions.…”
mentioning
confidence: 91%